2018
DOI: 10.1111/jgh.14008
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term liver stiffness assessment in hepatitis C virus patients undergoing antiviral therapy: Results from a 5‐year cohort study

Abstract: Stiffness declines significantly after achieving response, and the magnitude of decline is greater in the first year after treatment, while it tends to plateau from 1 year onwards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 23 publications
5
40
0
2
Order By: Relevance
“…Although there is ample evidence that supports the beneficial effect of HCV eradication on fibrotic regression, the relentless recover may not be taken for granted across all pupations and studies. The regression slop has been suggested to be very slow by non-invasive modalities 15 , 16 . It has also been reported that cirrhosis patients experience only 5% of net fibrosis improvement after 10 years of follow-up 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is ample evidence that supports the beneficial effect of HCV eradication on fibrotic regression, the relentless recover may not be taken for granted across all pupations and studies. The regression slop has been suggested to be very slow by non-invasive modalities 15 , 16 . It has also been reported that cirrhosis patients experience only 5% of net fibrosis improvement after 10 years of follow-up 15 .…”
Section: Discussionmentioning
confidence: 99%
“…More quantitative analyses, including immunostaining for cell-specific markers or morphometric analysis, may provide a future solution 20 , 36 . As noninvasive tests are widely applied in the directly acting antivirals (DAAs) era, accuracy is challenging and doubtful in the post-curative status 16 , 38 . Liver biopsy remains the gold standard to assess liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has 91% specificity and an 87% sensitivity for detecting cirrhosis [ 11 ]. A recent meta-analysis indicated that there is a greater reduction of the TE score after DAA therapy compared to IFN-based treatment, with some data indicating a 50% decline in the TE score 6 months after DAA therapy, followed by a slower decline over the subsequent 5 years [ 12 15 ]. It is thought that liver stiffness during chronic infection is a combination of hepatic inflammation and fibrosis, while after viral eradication the component of inflammation abates, followed by a slower phase of fibrosis regression.…”
Section: Introductionmentioning
confidence: 99%
“…The results were spectacular with respect to the presence of liver cirrhosis: it disappeared in half of the patients after 6 months and it was still present in just under 5% of them after 4 years of the end of therapy. Instead, if patients did not respond to treatment, the liver stiffness value declined slightly at its end (from 19.2 kPa to 18.1 kPa), after which it returned to the baseline value after half a year and then increased along time to 23.7 kPa at 5 years [48].…”
Section: Liver Stiffness -A Way To Monitor the Evolution Of Patients mentioning
confidence: 98%